Heart transplantation in the early phase of the COVID‐19 pandemic: A single‐center case series. Issue 9 (6th August 2020) - Hsu, Jeffrey J.; Al‐Saffar, Farah; Ardehali, Reza; Baas, Arnold S.; Carlson, Margrit; Cruz, Daniel; Deng, Mario; Fan, Ashley; Fraschilla, Stephanie; Gaynor, Pryce; Kamath, Megan; Kubak, Bernard M.; et al.
Abstract: The infectious disease coronavirus disease 2019 (COVID‐19) was declared a pandemic by the World Health Organization in March 2020. The impact of COVID‐19 on solid organ transplantations, including heart transplantation, is currently unclear. Many transplant programs have been forced to swiftly re‐evaluate and adapt their practices, leading to a marked decrease in transplants performed. This trend has been due to various factors, including increased donor COVID‐19 screening scrutiny and recipient waiting list management in anticipation of COVID‐19 critical care surge capacity planning. In the face of these unknown variables, determining when and how to proceed with transplantation in our population of patients with end‐stage cardiomyopathies is challenging. Here, we describe our center's experience with orthotopic heart transplantation (OHT) in one of the country's pandemic epicenters, where we performed eight OHTs in the first 2 months after community spread began in late February 2020.